FORMATION OF STUDENTS' READINESS FOR OF DIALOGICAL EDUCATION IN PEDAGOGICAL INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2002)
The means of the formation of students' readiness for dialogic training are introduced in the article. The author points out the methods of synthetic and analytic training give exercises for learning methods and for mastering practical skills of dialogic communication.